An update on: molecular genetics of high-risk chronic lymphocytic leukemia. Issue 2 (1st February 2020) - Moia, Riccardo; Patriarca, Andrea; Deambrogi, Clara; Rasi, Silvia; Favini, Chiara; Kodipad, Ahad Ahmed; Schipani, Mattia; Gaidano, Gianluca
ABSTRACT: Introduction : During the past few years, new genomic approaches have elucidated the molecular genetics of chronic lymphocytic leukemia (CLL) to a large extent. As a consequence, specific high-risk genetic features of the disease, e.g. TP53 disruption, have become the backbone of the treatment algorithm for CLL and serve as robust biomarkers for a precision medicine approach to this leukemia. Areas covered : This review covers the genetics of CLL and highlights the translational implications of molecular biomarkers that characterize patients with a high risk of disease progression. Knowledge of the genetic landscape of CLL has allowed the identification of the main molecular features associated with chemo-refractoriness, as well as resistance to BCR inhibitors and BCL2 inhibitors. The molecular basis of Richter transformation has also been characterized. Expert opinion : The term 'high risk CLL' has been changing over time, and might be subject to further changes in the future. With the advent of new therapeutic strategies targeting pathogenetic pathways of the disease, the definition is shifting from the historical view of refractoriness to chemo-immunotherapy, to refractoriness to BCR inhibitors and/or to BCL2 inhibitors. Patients failing these novel medicines are those for whom new therapeutic approaches are still highly needed.